El derecho a la información en materia electoral: el caso de Michoacán en la contienda a gobernador 2015 - Lykaris Carreño, Eunice Alexandra (Universidad Michoacana de San Nicolás de Hidalgo, 2016)
He following investigation thesis elucidates the right to the information in the electoral media pertaining to the campain for governor of Michoacan in 2015, through a quantitative analysis made according to the Organization of American States' (OAS) methodology. Another analysis was made, this time was a qualitative analysis, and it was made following the Critic Analysis of the Speech pertaining to the informative notes issued by state journals. It establishes that the right of the community to be well informed can only be observed through all of its faculties, the right to investigate, broadcast or transmit and the right to receive the information.

La siguiente tesis de investigación dilucida el derecho a la información en el ámbito electoral en la contienda a Gobernador de Michoacán 2015 a través de un análisis cuantitativo realizado mediante la metodología de la Organización de los Estados Americanos y otro cualitativo por medio del Análisis Crítico del Discurso de notas informativas expedidas en periódicos estatales. Se argumenta que el derecho a la comunidad a ser bien informado sólo puede observarse mediante todas sus facultades, el derecho a investigar, difundir y recibir información.
Facultad de Derecho y Ciencias Sociales. Maestría en Derecho de la Información
Keywords: info:eu-repo/classification/cti/5; FDCS-M-2016-1109; OEA; Análisis crítico del discurso; Periódicos; Notas informativas; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/741